Chinese music teachers value effectiveness, social, and facilitating factors over ease of use in ICT integration: A PLS-SEM study - Jun Jiang; Xiangming Zhang (PLoS ONE, 2025)
The integration of information and communication technology (ICT) in education has been widely acknowledged for its potential benefits. However, there is limited understanding of the factors influencing ICT integration among Chinese music teachers. This research explored technology acceptance among China’s music teachers via the unified theory of acceptance and use of technology (UTAUT) to bridge existing knowledge gaps. A survey was conducted with 83 music teachers who used ICT in their teaching. Partial least squares structural equation modelling with effect size estimation revealed that Chinese music teachers’ Behavioural Intention to use ICT was the strongest predictor of their actual Usage Behaviour. Performance Expectancy, Social Influence, and Facilitating Conditions positively influenced Behavioural Intention but did not directly impact Usage Behaviour, suggesting an indirect effect through shaping teachers’ willingness to use ICT. Effort Expectancy had no effect on either Behavioural Intention or Usage Behaviour, though multigroup analysis revealed this relationship varied by teacher age and experience. This study demonstrates the applicability of the UTAUT model in understanding ICT integration among Chinese music teachers. The findings highlight the need to prioritise demonstrating benefits of ICT, creating supportive environments, and providing adequate resources and training for ICT in music education, with implementation strategies tailored to teachers’ demographic characteristics. These findings suggest potential strategies for fostering technology integration in music education contexts.